ISU LINGKUNGAN PEMBANGUNAN JARINGAN TRANSMISI SUTT 150 KV PLTP KARAHA BODAS KE GI MALANGBONG, KABUPATEN TASIKMALAYA DAN GARUT, PROPINSI JAWA BARAT - -, Achmad Syafrudin (Bulletin of Scientific Contribution, 2010)
The plan construction Transmision line SUTT 150 KV of the PLTP Karaha Bodas at (Sub-District of Kadipaten) to Mainhouse Electricity Malangbong (Sub-District Malangbong) will raise effects to the environment. Identification are the stage of the potential impact before EIA study. Identification is one of the stage to get isues in the field to minimize all the effects that will appear in the future to support sustainable development.